The Influence of Student Worksheets Based on PBL-Mathematical Literacy on Problem-solving in Junior High Schools in Bengkulu - Izzati, Miftahul; Muchlis, Effie Efrida; Susanto, Edi; Patri, Sonya Fiskha Dwi; Kristiani, Febri; Stanggo, Pratiwi Disha (EDUPEDIA Publisher, 2025)
Purpose – Problem-solving is a key component in mathematics education, as emphasized by the NCTM. At SMAN 6 Kota Bengkulu, students’ performance in trigonometry remains low due to weak problem-solving skills and limited engagement. This study investigates the effect of the Problem-Based Learning (PBL) model, supported by mathematical literacy worksheets, on students’ mathematical problem-solving abilities. Methodology – A quasi-experimental design was employed using the Nonequivalent Posttest-Only Control Group Design. The population consisted of all 10th-grade students at SMAN 6 Bengkulu. Two classes were selected: Class XJ as the experimental group, taught using the PBL model with literacy-based worksheets, and Class XI as the control group, taught using a Cooperative Learning model. Data were collected through a mathematical problem-solving test and analyzed using an independent t-test. Findings – Results showed a significant difference in performance, with tvalue = 3.713 > tcritical = 1.673, indicating that the experimental group outperformed the control group in problem-solving ability. Novelty – This study offers a novel integration of PBL with mathematical literacy worksheets—an underexplored instructional approach in secondary trigonometry education. By combining content-specific literacy materials with a problem-based pedagogy, the study addresses a gap in research focused on enhancing higher-order thinking in mathematics. Significance – The findings provide empirical support for incorporating literacy-based, student-centered strategies in mathematics instruction. The study has implications for curriculum design aimed at improving problem-solving performance in similar educational contexts.